Recent advances in the in vitro and in vivo methods to assess impact of P‐glycoprotein and breast cancer resistance protein transporters in central nervous system drug disposition. (5th February 2023) - Chatterjee, Sagnik; Deshpande, Anup Arunrao; Shen, Hong
Abstract: One challenge in central nervous system (CNS) drug discovery has been ensuring the blood–brain barrier (BBB) penetration of compounds at an efficacious concentration that provides suitable safety margins for clinical investigation. Research providing for the accurate prediction of brain penetration of compounds during preclinical discovery is important to a CNS program. In the BBB, P‐glycoprotein (P‐gp) ( ABCB1 ) and breast cancer resistance protein (BCRP) ( ABCG2 ) transporters have been demonstrated to play a major role in the active efflux of endogenous compounds and xenobiotics out of the brain microvessel cells and back to the systemic circulation. In the past 10 years, there has been significant technological improvement in the sensitivity of quantitative proteomics methods, in vivo imaging, in vitro methods of organoid and microphysiological systems, as well as in silico quantitative physiological based pharmacokinetic and systems pharmacology models. Scientists continually leverage these advancements to interrogate the distribution of compounds in the CNS which may also show signals of substrate specificity of P‐gp and/or BCRP. These methods have shown promise toward predicting and quantifying the unbound concentration(s) within the brain relevant for efficacy or safety. In this review, the authors have summarized the in vivo, in vitro, and proteomics advancements toward understanding the contribution of P‐gp and/or BCRP in restricting the entry of compounds to the CNS of either healthy or special populations. Special emphasis has been provided on recent investigations on the application of a proteomics‐informed approach to predict steady‐state drug concentrations in the brain. Moreover, future perspectives regarding the role of these transporters in newer modalities are discussed. Abstract : An overview of the in vitro and in vivo methods to evaluate the role of P‐glycoprotein and breast cancer resistance protein in central nervous systems drug disposition. The recent advances in blood–brain barrier transporter proteomics and complex in vitro cell models predict future breakthroughs and innovations.